2017
DOI: 10.1071/rd16460
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of interleukin-11 expression in ovulatory follicles of the rat ovary

Abstract: The aim of the present study was to examine the regulation of interleukin (IL)-11 expression, as well as the role of IL-11, during ovulation in gonadotropin-primed immature rats. Injection of equine chorionic gonadotropin (eCG), followed by human CG (hCG) to induce superovulation stimulated expression of the Il11 gene in theca cells within 6h, as revealed by northern blot and in situ hybridisation analyses. Real-time reverse transcription-polymerase chain reaction analysis showed that the IL-11 receptor, α sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Previously, Liu et al 39 showed that the levels of Il6 mRNA were increased in both granulosa cells and COCs after hCG stimulation, and the treatment of IL6/its soluble receptor (IL-6SR) induced the expansion of mouse COCs, proposing that IL6 could act as a potent autocrine mediator involved in COC expansion. Jang et al 40 documented the localization of Il11 mRNA predominantly in the thecal layer of the rat ovary after hCG administration. In addition, the treatment of IL11 increased progesterone production in cultured rat preovulatory follicles 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Liu et al 39 showed that the levels of Il6 mRNA were increased in both granulosa cells and COCs after hCG stimulation, and the treatment of IL6/its soluble receptor (IL-6SR) induced the expansion of mouse COCs, proposing that IL6 could act as a potent autocrine mediator involved in COC expansion. Jang et al 40 documented the localization of Il11 mRNA predominantly in the thecal layer of the rat ovary after hCG administration. In addition, the treatment of IL11 increased progesterone production in cultured rat preovulatory follicles 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al 40 documented the localization of Il11 mRNA predominantly in the thecal layer of the rat ovary after hCG administration. In addition, the treatment of IL11 increased progesterone production in cultured rat preovulatory follicles 40 . Our current data demonstrated the localization of mRNA for Il6 and Il11 to granulosa and theca cells of preovulatory follicles and the compromised expression of these genes in the mutant mouse ovary.…”
Section: Discussionmentioning
confidence: 99%
“…The role IL-11 plays in folliculogenesis and/or oocyte development was not clear until Jang et al [43] examined the regulation of IL-11 expression as well as the role of IL-11 during ovulation. They observed that LH stimulated the expression of IL-11 protein in theca cells and LH-stimulated IL-11 mRNA levels were repressed by protein kinase A and mitogen-activated protein kinase inhibitors (Table 4).…”
Section: Gynaecological and Other Cancersmentioning
confidence: 99%
“…This is by far the only study that has revealed for the first time the regulation and the role of IL-11 expression during ovulation. IL-11 in theca cells is activated by mitogen-activated protein kinase signaling and TLR4 activation, leading to enhanced progesterone production during ovulation [43] (Table 3).…”
Section: Gynaecological and Other Cancersmentioning
confidence: 99%
“…IL-11 is primarily an anti-inflammatory cytokine that was initially described as a growth factor in hematopoiesis, driving megakaryocyte differentiation and synergizing with other factors (reviewed by Du and Williams 24 ). IL-11 is produced in preovulatory follicles by theca cells in response to LH and stimulates progesterone production and follicle development 25 . LIF was first described as a protein factor that induces differentiation in M1 murine myeloid leukemic cells 26 .…”
mentioning
confidence: 99%